IMPLIKASI PENERAPAN SISTEM CORETAX TERHADAP KEPATUHAN PAJAK PADA PT. PELNAS BARUNA JAYA DI KOTA BATAM - Hidayatullah, Syarif; Candra, Hendra; Azzahra, Sitti Aliyah; Arza, Zubair; Azzahra, Putri Nadira (POLITEKNIK LP3I JAKARTA, 2026)
The Taxation is one of the main pillars of state revenue that supports national development, However, tax compliance in Indonesia is still a big challenge, especially for companies located in the country's border areas. The purpose of this study is to explore how CoreTax system affects the tax compliance, identify the challenges, and analyze the implications. This research uses a qualitative approach with a case study design, through in-depth interviews, documentation studies and field observations. The data was analyzed thematically based on Technology Acceptance Model (TAM), tax compliance theory, and Institutional Theory. The results of this study show that the implementation of CoreTax initially faced of limited digital literacy and technical understanding, but it continuously increased with full support from DJP tax institution. CoreTax has been proven to make easy and simplify reporting, increase transparency, and strengthen the actual compliance through an automated sanctions mechanism. In addition to the technical aspects, institutional legitimacy and trust in the DJP tax institution have also proven to play an important role in shaping compliance morale. This research has practical implications for government to strengthen the digital infrastructure, provide technical guidance, and expand the socialization in areas with limited access to technology. From an academic perspective, these findings enrich the literature on CoreTax's digital taxation system that supports sustainable tax compliance.